The Long-Term Effect of a Nine Amino-Acid Antimicrobial Peptide AS-hepc3(48-56) Against Pseudomonas aeruginosa With No Detectable Resistance - Zhu, Depeng; Chen, Fangyi; Chen, Yan-Chao; Peng, Hui; Wang, Ke-Jian (Frontiers in Cellular and Infection Microbiology, 2021)
The emergence of multidrug-resistant (MDR) pathogens has become a global public health crisis. Among them, MDR Pseudomonas aeruginosa is the main cause of nosocomial infections and deaths. Antimicrobial peptides (AMPs) are considered as competitive drug candidates to address this threat. In the study, we characterized two AMPs (AS-hepc3(41-71) and AS-hepc3(48-56)) that had potent activity against 5 new clinical isolates of MDR P. aeruginosa. Both AMPs destroyed the integrity of the cell membrane, induced leakage of intracellular components, and ultimately led to cell death. A long-term comparative study on the bacterial resistance treated with AS-hepc3(41-71), AS-hepc3(48-56) and 12 commonly used antibiotics showed that P. aeruginosa quickly developed resistance to the nine antibiotics tested (including aztreonam, ceftazidime, cefepime, imipenem, meropenem, ciprofloxacin, levofloxacin, gentamicin, and piperacillin) as early as 12 days after 150 days of successive culture generations. The initial effective concentration of 9 antibiotics against P. aeruginosa was greatly increased to a different high level at 150 days, however, both AS-hepc3(41-71) and AS-hepc3(48-56) maintained their initial MIC unchangeable through 150 days, indicating that P. aeruginosa did not produce any significant resistance to both AMPs. Furthermore, AS-hepc3(48-56) did not show any toxic effect on mammalian cells in vitro and mice in vivo. AS-hepc3(48-56) had a therapeutic effect on MDR P. aeruginosa infection using a mouse lung infection model and could effectively increase the survival rate of mice by inhibiting bacterial proliferation and attenuating lung inflammation. Taken together, the short peptide AS-hepc3(48-56) would be a promising agent for clinical treatment of MDR P. aeruginosa infections.